Chinese university English-major students' attitude toward literature circles and literature reading - Ma, Lei; Ismail, Lilliati; Saharuddin, Norzihani (Society for Research and Knowledge Management, 2023)
Of the four basic skills, namely, reading, is a fundamental tool that supports the Development of other skills. In Chinese tertiary education, reading is a compulsory core subject for students. Although the benefits of teaching English reading through literature circles have been recognized in other countries for decades, there is still an insufficient practice of this activity among English-major students in the Chinese university context. This study aims to investigate the attitudes of Chinese English-major students toward literature circles as a method of teaching reading, and to determine the benefits of reading literature in language learning. The study employs a one-shot case study involving only one group exposed to the treatment, followed by a measure. Quantitative and qualitative data were collected to determine the participants' attitudes toward literature circles and their perception of the benefits of reading literature. An intact class of 41 students participated in this extracurricular reading activity through the convenience sampling method. The result obtained from the eight closed-ended questions indicated that the participants generally held favorable views toward literature circles. The results from the focus group interviews confirmed the benefits of reading literature in terms of cultural, linguistic, and personal enrichment. The findings suggest that more longitudinal studies involving comparison groups or qualitative studies are necessary to better understand the benefits of literature circles.